Effects of alginate oligomer on the expression of cell cycle- and stress-related genes in Chlamydomonas reinhardtii. Issue 6 (3rd June 2017) - Ueno, Mikinori; Nishiguchi, Tomoki; Takeshita, Satoshi; Yamaguchi, Kenichi; Oda, Tatsuya
Abstract: Enzymatically prepared alginate oligomer (AO) promoted the growth of Chlamydomonas reinhardtii in a concentration-dependent manner. AO at 2.5 mg/mL induced increase in expression levels of cyclin A, cyclin B, and cyclin D in C. reinhardtii . CuSO4 at 100 μM suppressed the growth of C. reinhardtii n, and AO at 2.5 mg/mL significantly alleviated the toxicity of CuSO4 . Increased intracellular reactive oxygen species level in C. reinhardtii induced by CuSO4 was reduced by AO. After cultivation with CuSO4 at 100 μM, expression levels of ascorbate peroxidase and superoxide dismutase in C. reinhardtii were increased, and AO reduced the increased levels of these enzymes. These results suggest that AO exhibits beneficial effects on C. reinhardtii through influencing the expression of various genes not only at normal growth condition but also under CuSO4 stress. Abstract : :